2013
DOI: 10.1007/s10071-013-0674-3
|View full text |Cite
|
Sign up to set email alerts
|

When less is more: like humans, chimpanzees (Pan troglodytes) misperceive food amounts based on plate size

Abstract: We investigated whether chimpanzees (Pan troglodytes) misperceived food portion sizes depending upon the context in which they were presented, something that often affects how much humans serve themselves and subsequently consume. Chimpanzees judged same-sized and smaller food portions to be larger in amount when presented on a small plate compared to an equal or larger food portion presented on a large plate, and did so despite clearly being able to tell the difference in portions when plate size was identica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
82
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(93 citation statements)
references
References 58 publications
9
82
2
Order By: Relevance
“…The study of Parrish and Beran (2013), using the simultaneous discrimination task, also appearred to demonstrate the illusory tendency of chimpanzees: they simultaneously showed their chimpanzees a circular-shaped food (IS) on a larger circular dish (OS) and on a smaller circular dish. The chimpanzees tended to choose the latter more frequently, thus suggesting that chimpanzees perceive a version of the Delboeuf illusion like humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Parrish and Beran (2013), using the simultaneous discrimination task, also appearred to demonstrate the illusory tendency of chimpanzees: they simultaneously showed their chimpanzees a circular-shaped food (IS) on a larger circular dish (OS) and on a smaller circular dish. The chimpanzees tended to choose the latter more frequently, thus suggesting that chimpanzees perceive a version of the Delboeuf illusion like humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies of the Delboeuf illusion involving humans have focused on how humans perceive this illusion under various conditions (e.g., Cooper & Weintraub, 1970;Goto et al, 2007;Weintraub & Schneck, 1986), few studies regarding this illusion have been conducted with nonhumans. Chimpanzees (Parrish & Beran, 2013), rhesus monkeys, and capuchin monkeys (Parrish, Brosnan, & Beran, 2015) perceive the Delboeuf illusion as humans do; furthermore, although pigeons perceive this illusion as well, their tendency is contrary to that of humans (Hyuga, Kaneko, & Fujita, 2014). Such inconsistency is often observed in comparative studies of geometric illusions such as the Ebbinghaus and the Zöllner illusions (see Fujita, Nakamura, Watanabe, & Ushitani, in press).…”
mentioning
confidence: 99%
“…For our purposes, we created a task for the chimpanzees to match that used with humans in which portions on small plates were reported to be larger than the same portions served on large plates. Like humans, chimpanzees made the same mistake in overestimating food quantity on small plates compared to large plates (Parrish & Beran, 2014b). The chimpanzees chose between round slices of food or piles of cereal pieces (Figure 2).…”
Section: Biases and Context Effectsmentioning
confidence: 99%
“…Susceptibility to this illusion has not been found in non-primate species. A recent study used the same methodological approach (spontaneous choice test with food portions as stimuli) adopted by Parrish and Beran (2014) to investigate dogs' sensitivity to the Delboeuf illusion. Control trials showed that dogs tried to maximize food intake, but no preference for either plate was shown in test trials with the illusory pattern, suggesting that dogs do not perceive the Delboeuf illusion .…”
mentioning
confidence: 99%
“…Parrish and Beran (2014) used the natural tendency of chimpanzees to reach for the larger food portion to assess the perception of the Delboeuf illusion in three adult subjects. Two different-sized food portions were presented on two identical plates in control trials in which subjects were expected to select the larger portion.…”
mentioning
confidence: 99%